A couple of chimeric twins generated from A possible intrauterine cell exchange. Issue 1 (December 2019) - Corradi, Dante; Locarno, Laura; Marino, Miguel
Abstract: Chimerism is the presence of two or more genetically distinct cell lines in an organism. The presence of blood Chimerism in human twins is rare and was first described by Dunsford in 1953 [2] who discovered a mixture of two blood types in a donor. The only way some chimeras can be distinguished from non-chimeras is through DNA testing. In 2017 in the context of a sex assault, a blood sample came to our Forensic Genetic Laboratory. When analyzed with STRs and the results were confirmed, the obtained profile surprised us. A mixed profile was observed, with up to 4 alleles per marker and imbalances. After evaluating and confirming that it wasn't a contamination, this aroused our interest in deepening the study. We were able to find out that the individual to whom the sample belonged had a twin brother. After obtaining the consent of both individuals more samples were taken for further studies. Blood, hair and nails of both were analyzed with different autosomal, Y and X chromosome markers. In hair samples we obtained single male profiles, but in blood samples these profiles were mixed together in different proportions. Those alleles present in the hair samples of one subject where the minor contributor in the blood profile of his sibling and vice versa . We present a brief summary of the case context and explain the results of DNA markers that we used.